Implementation of the right to health through vaccination - Itasari, Endah Rantau; Erwin; Bangun, Budi Hermawan; Sagio, Ibrahim; Purwanti, Evi; Elida, Sri Agustriani; Wulandari, Ria; Darajati, Muhammad Rafi; Kinanti, Fatma Muthia; Arsensius; Thomas, Silvester (University of Islam Malang, 2024)
Health is regarded as a basic human need Health is a fundamental right recognized in various international human rights instruments, such as the Universal Declaration of Human Rights and the International Covenant on Economic, Social and Cultural Rights. The World Health Organization (WHO) has declared COVID-19 a global public health pandemic on January 30, 2020. Based on the data collected, there are still members of the community who have not received the Covid-19 Booster vaccine even though it is urgently given as an antiviral. Therefore, as part of an effort to increase the coverage of vaccination, it is necessary to implement a Covid-19 public dedication as the fulfilment of the right to health. The method of community-based participatory research (Community Based Participatory Research, CBPR) is implemented. The results of the vaccination activities carried out at Tanjungpura University Faculty of Law can contribute to the vaccine coverage that exists in the community. As for the number of participants of the activity was 172 (one hundred seventy-two) people consisting of 117 (a hundred seventeen) students and 61 (sixty-one) the general public. In addition, there are students and members of the community who have not received the Covid-19 Booster Vaccine while the delivery is very urgent as an anti-virus, even there are those who have never received the vaccine at all.